⌊ 3 2 0 ⌋ + ⌊ 3 2 1 ⌋ + ⌊ 3 2 2 ⌋ + ⋯ + ⌊ 3 2 1 0 0 0 ⌋
The expression above can be expressed as C 2 A − B , where A , B , C are positive integers. Find the minimum possible value of A + B + C .
Notation:
⌊
⋅
⌋
denotes the
floor function
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just a note: your expression is not unique (imagine increasing A by 1 and B by a lot, or adding 1 to A and doubling B and C ). Maybe specifying the minimum value of A + B + C would remove any ambiguity?
You are a person with rigorous thought.
I was wondering whether it was unique when posting...thanks!
So, the given number, call it N, equals the expression with A=1001, B=1502 and C=3, adding up to 2506. Of course, that's not the only solution for A, B and C. But why is it the best?
Sketch of a proof: 3N is very close under 2^1001. Then 6N is very close under 2^1002, 12N is very close under 2^1003 and so on. CN needs to be close under 2^A so that B is small enough.
If C is one of 3, 6, 12, ... (3×2^k), (only considering up to 1536 with k=9) then "very close" means B is less than a million. Considering bigger values for C would mean A+C being already too big
But if C is over 3 and not one of them, CN is below a power of 2 by an additional (multiple of) N, which is HUGE, making B huge.
But C being 6, 12, 24, ..., so even, would mean even B and they could then be reduced to A-1, B/2, C/2. Same goes if we try C=2.
C=1 is no good either, as N is about a third way between 2^999 and 2^1000, making B huge again.
Letting q k = ⌊ 3 2 k ⌋ , division by 3 yields: 2 k = 3 q k + r k with r k ∈ { 1 , 2 } since 2 and 3 are coprime. Now observe that doubling equation above gives 2 k + 1 = 2 ( 3 q k + r k ) = 6 q k + 2 r k = { 3 ⋅ 2 q k + 2 3 ⋅ ( 2 q k + 1 ) + 1 if r k = 1 if r k = 2 . Then r k + r k + 1 = 3 and q k + q k + 1 = 3 2 k − r r + 3 2 k + 1 − r k + 1 = 3 2 k ( 2 + 1 ) − 3 = 2 k − 1 .
Using that yields k = 0 ∑ 1 0 0 0 ⌊ 3 2 k ⌋ = 2 1 ( k = 0 ∑ 1 0 0 0 q k + ℓ = 0 ∑ 1 0 0 0 q ℓ ) = 2 1 ( k = 0 ∑ 1 0 0 0 q k + k = 0 ∑ 1 0 0 0 q k + 1 ) − 2 1 q 1 0 0 1 = 2 1 k = 0 ∑ 1 0 0 0 ( q k + q k + 1 ) − ( 6 2 1 0 0 1 − r 1 0 0 1 ) = 2 1 k = 0 ∑ 1 0 0 0 ( 2 k − 1 ) − ( 6 2 1 0 0 1 − r 1 0 0 1 ) = 6 3 ⋅ ( 2 1 0 0 1 − 1 − 1 0 0 1 ) − 6 2 1 0 0 1 − r 1 0 0 1 = 6 2 ⋅ 2 1 0 0 1 − ( 3 ⋅ 1 0 0 2 − r 1 0 0 1 ) . Since r 0 = 1 , we get r 1 0 0 0 = 1 and r 1 0 0 1 = 2 , we get 6 2 ⋅ 2 1 0 0 1 − ( 3 ⋅ 1 0 0 2 − r 1 0 0 1 ) = 6 2 ⋅ 2 1 0 0 1 − ( 3 ⋅ 1 0 0 2 − 2 ) = 3 2 1 0 0 1 − ( 3 ⋅ 5 0 1 − 1 ) = 3 2 1 0 0 1 − 1 5 0 2 Therefore 3 2 1 0 0 1 − 1 5 0 2 = C 2 A − B leads to A + B + C = 1 0 0 1 + 1 5 0 2 + 3 = 2 5 0 6 , which is minimal since the numerator is even and denominator odd.
Problem Loading...
Note Loading...
Set Loading...
Consider the general term of summand:
a n = ⌊ 3 2 n ⌋ = ⌊ 3 ( 3 − 1 ) n ⌋ = ⌊ 3 ( 3 n − ( n ) 3 n − 1 + n ( n − 1 ) 3 n − 2 − ⋯ + ( − 1 ) n − 1 ⋅ 3 + ( − 1 ) n ⌋ = ⌊ 3 n − 1 − ( n ) 3 n − 2 + n ( n − 1 ) 3 n − 3 − ⋯ + ( − 1 ) n − 1 + 3 ( − 1 ) n ⌋ = 3 n − 1 − ( n ) 3 n − 2 + n ( n − 1 ) 3 n − 3 − ⋯ + ( − 1 ) n − 1
⟹ a n = ⎩ ⎪ ⎨ ⎪ ⎧ 3 2 n − 3 1 3 2 n − 3 2 if n is even. if n is odd. = 3 2 n − 2 1 + 6 ( − 1 ) n
Therefore,
S = n = 0 ∑ 1 0 0 0 ⌊ 3 2 n ⌋ = n = 0 ∑ 1 0 0 0 ( 3 2 n − 2 1 + 6 ( − 1 ) n ) = 3 1 ( 2 − 1 2 1 0 0 1 − 1 ) − 2 1 0 0 1 + 6 1 = 3 2 1 0 0 1 − 1 5 0 2 Note: n = 0 ∑ m 6 ( − 1 ) n = { 6 1 0 if m is even. if m is odd.
⟹ A + B + C = 1 0 0 1 + 1 5 0 2 + 3 = 2 5 0 6